Literatura e história em quadrinhos (HQ) na educação básica - Santos, Wanderley Alves dos (2015)
The reading training in basic education has been a challenge in contemporary society, characterized by digital practices and by the abundance of visual elements, which requires expanding the possibilities of discursive genres approach, among which the literary genre is included. The literature - as well as many other art expressions - is understood as a right of the human being, as it is vital and transformative (CANDIDO, 2010), and because of that, it needs to become, effectively an object of practices mediated by school where, according to, many children and young people, it is a place of unique access to literary reading. The present research is about the possibility of ensuring that young students can experience aesthetic experiences, by investigating and proposing the interdisciplinary dialog between literature, especially the classic ones and the arts, in the form of comics. The access to many artistic languages, interacting with the visual culture must be a school concern (BARBOSA, 2010). Immersed in a broad universe of visual culture to which the contemporary people are exposed, the comics as a subject can be addressed in the school as a possibility of approximating the visual arts, in dialog with the literature. Based on assumptions that guide the pedagogical action in teaching visual arts and literature, the concept of literary literacy (PAULINO; COSSON, 2009), and by the notion of semiosis (SANTAELLA, 2012), this research presents a reading project involving the novel Dom Casmurro written by Machado de Assis, and two versions of the same literary work in a comic version, developed with students from high school. The project implementation, developed in the form of didactic sequence, indicates the confirmation of the hypothesis that the association between the subjects; literature and visual arts can draw young students attention to the literary readings, and it also leads students to artistic appreciation, adding to the effective aesthetic experience in the educational field and to the reading training. This mentioned production in comic of formatted, presented as an appendix in this paper, and represents the didactics sequence research product.